The effects of emotions on the disposition to normative and non-normative political action in the context of the Chilean post-social outburst - Hatibovic, Fuad; Sandoval, Juan; Faúndez, Ximena; Gaete, Jose-Manuel; Bobowik, Magdalena; Ilabaca, Paola (Frontiers in Psychology, 2023)
This article analyzes the role of Chileans’ emotions as predictors of normative and non-normative political action in the context of the post-social outbreak and the constituent process. We carried out three descriptive studies: first, a study conducted 1 year after the social outburst (n = 607), a second one carried out before the constitutional referendum (n = 320), and a third study conducted after the constitutional referendum (n = 210). The results indicated that participants present a higher disposition to normative over non-normative political action, although both lose strength as the studies temporally move away from the social outburst. Also, our research established that emotions directed towards different events related to the Chilean political process play a conspicuous role in predicting the disposition to mobilize in a normative and non-normative way.